Pengaruh Pemberian Temulawak (Curcuma xanthorriza Roxb) Terhadap Kelulushidupan Ikan Mas (Cyprinus carpio L) Setelah Di Infeksi Aeromonas hydrophila - Sari, Novita Winda; Lukistyowati, Iesje; Aryani, Nety (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
The Effect Of Curcuma (Curcuma xanthorrhiza Roxb) On Survival RateOf Carp Fish (Cyprinus carpio L) After Infected Aeromonas hydrophila. Thestudy was conducted from February to March 2012 in the Laboratory of ParasiticDiseases of Fish and Fisheries and Marine Sciences Faculty of the RiauUniversity. The purpose of this study was to determine the effect of giving asolution of curcuma (Curcuma xanthorriza Roxb) on survival rate of carp(Cyprinus carpio L) after the infected A. hydrophila. This study uses fivetreatments, 1) Kp: positive control (without solution of curcuma and the infectionof A. hydrophila), 2) Kn: negative control (without a solution of curcuma andwithout the infection with A. hydrophila), 3) P1: Curcuma solution with aconcentration of 0.2 g / l, 4) P2: Curcuma solution with a concentration 0.4 g/l, 5)P3: Curcuma solution with a concentration of 0.6 g / l. Providing a solution ofcurcuma with a concentration 0.6 g / l gives the best effect on the survival rate of100%, growth in the absolute weight of 12.48 g / fish and daily growth rate of2.39%.